Going beyond systematic reviews: realist and meta-narrative reviews - Otte-Trojel, T; Wong, G (IOS Press, 2016)
Health information technologies are complex interventions whose effects differ across contexts. To improve our understanding of the effects of health information technologies, approaches are needed that utilize evidence beyond experimental results in order to provide explanatory answers to how and why a given technology works. The relatively new realist and meta-narrative review approaches are introduced as important methods in synthesising and analysing evidence in the field of health informatics. A common purpose of these two review approaches is to help create a sense of evidence about complex interventions that enables an understanding of how and why they work. A detailed description of the principles and objectives of the two types of reviews is presented. Key steps required to conduct each of the reviews are summarized, and examples of how the review approaches have been applied to topics related to health informatics are provided. Limitations of the two review approaches are discussed.